The Native Production of the Sesquiterpene Isopterocarpolone by Streptomyces sp. RM-14-6 - Shaaban, Khaled A. (2013)
We report the production, isolation and structure elucidation of the sesquiterpene isopterocarpolone from an Appalachian isolate Streptomyces species RM-14-6. While isopterocarpolone was previously put forth as a putative plant metabolite, the current study highlights the first native bacterial production of isopterocarpolone and the first full characterization of isopterocarpolone using 1D and 2D NMR spectroscopy and HR-ESI mass spectrometry. Considering the biosynthesis of closely related metabolites (geosmin or 5-epiaristolochene), the structure of isopterocarpolone also suggests the potential participation of one or more unique enzymatic transformations. In this context, this work also sets the stage for the elucidation of potentially novel bacterial biosynthetic machinery.